PENGARUH MOTIVASI, PENGALAMAN KERJA DAN PENGAWASAN TERHADAP KINERJA TENAGA KEPENDIDIKAN PADA UNIVERSITAS KATOLIK SANTO THOMAS - Simangunsong, Elisabeth; Sinaga, Desputri Frnasisca (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research aims to test and analyze the influence of motivation, work experience and supervision on the performance of educational staff at Santo Thomas Catholic University, Medan. Data collection was carried out on a population of 72 people with a sample of 42 people obtained using the Slovin technique and determined using the stratified random sampling method. Data analysis used SPSS version 25. The data analysis techniques used in this research were validity, reliability, multiple linear regression analysis and hypothesis testing (t test and f test). From the partial test results, the t test shows that the t value is 7.720 > ttable 1.686 with a significance level of 0.000 < 0.05, that motivation has a positive and partially significant effect on the performance of educational staff. Likewise, work experience shows tcount of 9.315 > ttable 1.686 with a significant level of 0.000 <0.05, that Work experience has a partially positive and significant effect on the performance of educational staff. Furthermore, the t test on supervision shows that the t value is 3.535 > t table 1.686 with a significance level of 0.001 < 0.05, that supervision has a positive and partially significant effect on the performance of educational staff. The F test shows that motivation, work experience and supervision simultaneously have a significant effect on the performance of educational staff at Santo Thomas Catholic University, Medan. With a value of Fcount of 52.072 > Ftable of 3.24 with a significance level of 0.000 < 0.05. The results of this research conclude that the multiple linear regression equation is Y= 0.089 + 0.268MO + 0.453PK + 0.139P + e. This means that motivation, work experience and supervision have a partially positive and significant effect on the performance of educational staff at Santo Thomas Catholic University, Medan.The coefficient of determination (R square) value is 0.804 or 80.4%, meaning that the performance of educational staff can be explained by motivation, work experience and supervision. Meanwhile, 19.6% can be explained by other variables not included in this research such as discipline and workload.